Governing by Evaluation: Setting the Scene - Christina Segerholm; Linda Rönnberg; Joakim Lindgren; Agneta Hult (Springer, 2025)
This introductory chapter starts by outlining the aim of the book: to analyse and discuss the interplay between governing, evaluation and knowledge with an empirical focus on Swedish higher education. It then goes on to locate this aim and the intended contribution within the wider research context and in previous studies. The chapter also highlights some important national traits of the Swedish case and Swedish higher education policy development, before presenting the overall conceptual frame employed in the book and the project it builds on. Finally, an outline of the forthcoming chapters is provided.
Evaluation-Knowledge Nexus : Swedish Higher Education as a Case